Characterisation and bioactivity analysis of exopolysaccharides from Lactiplantibacillus plantarum L3 - Jingyan Zhang; Tao Hu; Yuying Ma; Yiming Ma; Qingshen Sun (Carbohydrate Polymer Technologies and Applications)
This study systematically investigated the structural characteristics and functional properties of exopolysaccharides (EPS) produced by Lactiplantibacillus plantarum L3, focusing on their immunomodulatory and antioxidant potential. The EPS, with a molecular weight (Mw) of 79.93 kDa, was composed of diverse monosaccharides, including d-glucose, d-glucosamine, d-mannose, d-galactose, l-rhamnose, d-xylose, d-glucuronic acid, d-galacturonic acid, l-fucose, l-guluronic acid, d-mannuronic acid, and d-ribose, in molar ratios of 397.403: 236.233: 148.526: 52.448: 46.485: 25.344: 6.902: 4.290: 2.158: 1.533: 1.117:0.619: 0.545. Structural analyses using FT-IR, Raman and NMR revealed the presence of both α- and β-glycosidic bonds, while X-ray diffraction indicated an amorphous structure. The Congo red assay confirmed a triple-helix conformation, and scanning electrical microscopy (SEM) and atomic force microscopy (AFM) imaging demonstrated a highly branched and rough surface morphology. Thermal analysis revealed EPS decomposition at 216.33 °C and 260.45 °C, indicating good thermal stability. In vitro experiments using RAW264.7 cells demonstrated that EPS (200–400 µg/mL) significantly enhanced nitric oxide (NO) production and pro-inflammatory cytokine secretion (TNF-α and IL-6), while also increasing the activities of antioxidant enzymes (SOD, CAT, and GSH-Px), highlighting its potent antioxidant capacity. At a higher concentration (600 µg/mL), EPS exhibited anti-inflammatory effects by promoting IL-10 secretion, suggesting a balanced immunomodulatory function. These findings underscore the potential of L. plantarum L3 EPS as a promising postbiotic agent with dual antioxidant and immunomodulatory properties.